Program Policy Implementation Community Development and Empowerment (Pro Bebaya) in Samarinda City - Asnar, Asnar (Interdisciplinary Social Studies, 2023)
Background: Before the existence of Pro Bebaya,  in Samarinda City  itself it was felt that these two activities were very slow due to limited funds and also limited numbers (roads and drainage for development activities and the number of people fostered in community empowerment activities) that could be carried out in 1 year. Aim: This study aims to determine the implementation of community development and empowerment program (Pro Bebaya) policy in Sungai Dama Village, Samarinda Ilir District, Samarinda City, along with its supporting and inhibiting factors. Method: The research is qualitative. Sampling technique with purposive sampling technique and accidental sampling technique. Data collection techniques, namely in-depth interviews, participatory observation, and documentation studies. As for data analysis techniques, namely Miles and Huberman's interactive model data analysis techniques. Findings: The results of the study are 1) Implementation of Pro Bebaya Policy in Sungai Dama Village, Samarinda Ilir District, Samarinda City in terms of 4 indicators, namely Input, Process, Output, and Outcome. Input related to the budget and available human resources. The process relates to the procedure for implementing activities starting from planning, budgeting, to evaluation. Output with respect to the activities carried out, and Outcomes with respect to the direct impact of the implementation of activities. 2) Supporting factors for the implementation of Pro Bebaya in Sungai Dama Village, Samarinda Ilir District, Samarinda City, namely full support from the Mayor of Samarinda, because Pro Bebaya is one of the 9 Priority Programs of the Mayor of Samarinda.